Intimate partner violence :a resource for professionals working with children and families - Giardino, Angelo P (STM Learning, 2010)
"Intimate Partner Violence includes in-depth analyses of every aspect of IPV, including contemporary concepts and research on its prevalence, nature, causes, and impact"--Provided by publisher.